Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Nelayan Jaring Insang Dasar di Desa Lawulo, Kecamatan Samaturu, Kabupaten Kolaka - Saleh, Ramlah; Amin, Muhtar; Prihantini, Campina Illa (Politeknik Negeri Sambas, 2023)
Kolaka Regency is one of the fisheries producers in Southeast Sulawesi Province. The economic value of capture fisheries in Kolaka Regency also continues to increase from year to year. Unfortunately, this increase is not followed by an improvement in the economy of small-scale fishermen. Many factors influence this. One of them is the still high practice of using simple fishing gear and the management of fisheries businesses that are not yet qualified. Lawulo Village has people whose main livelihood is fishing. In general, they use gill nets in their capture fisheries business. This study uses multiple linear regression analysis intending to know the factors that influence the income level of gillnet fishermen. The data used is primary data obtained from interviews with fishermen. The results showed that four factors significantly influenced the income level of basic gillnet fishermen, namely age and education level. The variable number of family dependents and business experience did not significantly affect the income received by fishermen.